Relation of salivary calcium, phosphorus and alkaline phosphatase with the incidence of dental caries in children - Vijayaprasad K; Ravichandra K; Vasa A.A.K; Suzan S (Wolters Kluwer Medknow Publications, 2010)
Aim: The purpose of this study was to assess possible relationship of Calcium, Phosphorus and Alkaline-phophatase levels in saliva with incidence of caries in child patients. Settings and Design: Children (n=75) attending Department of Pedodontics, St. Joseph Dental college, Eluru, with and without caries were categorized in to Group I: Consisting of 25 children with non-rampant caries, Group II: Consisting of 25 children with rampant caries, Group III: Consisting of 25 children without caries. (Control group). Materials and Methods: The samples of saliva were collected one week after oral prophylaxis. Unstimulated directly expectorated whole saliva samples were collected in clean, dry, sterilized glass bottles and fitted with proper rubber stoppers immediately. The samples were subjected to biochemical assay for estimation of calcium, phosphorus and alkaline phosphatase levels. Statistical analysis used: ANOVA. Results: The alkaline Phosphatase activity for rampant caries group was 18.66 K.A, and control group was 4.68 K.A. The values of alkaline phosphatase activity for minimal caries group was 6.16 KA. Conclusion: Saliva could reflect a caries risk situation was supported by the fact that alkaline phosphatase activity was very much significantly higher in caries prone groups.